Cytotoxicity of root canal irrigating solutions and photodynamic therapy using curcumin photosensitizer - Strazzi-Sahyon, H. B. [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Nakao, J. M. [UNESP]; Takamiya, Aline Satie [UNESP]; Queiroz, I. O.A. [UNESP]; Santos, Paulo Henrique dos [UNESP]; Oliveira, Sandra Helena Penha de [UNESP]; Araújo, Gustavo Sivieri de [UNESP] (Elsevier, 2022)
Background: Photodynamic therapy (PDT) has shown satisfactory antibacterial effects. However, little information regarding the cytotoxicity potential of PDT using curcumin as a photosensitizer (PS) on fibroblasts are found. The aim of this in vitro study was to evaluate the cytotoxicity of root canal irrigating solutions and photodynamic therapy with curcumin PS on the L-929 cell line. Methods: Healthy mouse skin fibroblast cells were distributed into the following 7 experimental groups: G1 – culture medium DMEM (control group); G2 – 0.9% sodium chloride; G3 – 2.5% sodium hypochlorite (NaOCl); G4 – 5% NaOCl; G5 – PDT with curcumin PS at 500 mg/L + blue LED; G6 – PDT with curcumin PS at 750 mg/L + blue LED; and G7 - PDT with curcumin PS at 1000 mg/L + blue LED. All experimental groups which underwent PDT action were submitted to blue LED for 4 min, with a wavelength of 480 nm and energy fluency of 75 J/cm². The cultures were maintained under standard cell culture conditions (37°C, 100% humidity, 5% CO2). Cell viability analysis was performed using the colorimetric method to evaluate the periods of 6, 24, and 48 h. Data were subjected to the Kruskal–Wallis test, followed by the Dunn test to compare groups and Friedman test to compare periods (α = 0.05). Results: When comparing the periods, no significant differences were observed for any of the experimental groups analyzed (p > 0.05), except for the NaOCl2.5 group that exhibited higher cell viability at 6 h compared to the period of 48 h (p = 0.0489). In the comparisons of the experimental groups, there were no statistically significant differences between the control group compared to all disinfection protocols, regardless of the period evaluated (p > 0.05), except for the PDT + C1000 group that showed lower cell viability (P < 0.05). Conclusions: PDT with curcumin at 1000 mg/L was cytotoxic on L-929 fibroblast cell culture. However, laser-activated curcumin at a concentration of 500 mg/L presented no influence on L-929 fibroblast cell viability in in vitro conditions.
Keywords: Curcumin; Cytotoxicity; Fibroblasts; Photodynamic therapy; Root canal irrigants; Root canal therapy